2017
DOI: 10.1111/age.12541
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction of reproduction traits for Merino sheep

Abstract: Economically important reproduction traits in sheep, such as number of lambs weaned and litter size, are expressed only in females and later in life after most selection decisions are made, which makes them ideal candidates for genomic selection. Accurate genomic predictions would lead to greater genetic gain for these traits by enabling accurate selection of young rams with high genetic merit. The aim of this study was to design and evaluate the accuracy of a genomic prediction method for female reproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
3
10
1
4
Order By: Relevance
“…However, it is important to consider that Puledda et al (2017) reported moderate-high phenotypic correlations between ILCY and MCP related traits, positive with the RCT/logK20 traits (range 0.32-0.64) and negative with A30 (-0.34, -0.67, respectively for the phenotypic and genotypic correlations).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is important to consider that Puledda et al (2017) reported moderate-high phenotypic correlations between ILCY and MCP related traits, positive with the RCT/logK20 traits (range 0.32-0.64) and negative with A30 (-0.34, -0.67, respectively for the phenotypic and genotypic correlations).…”
Section: Discussionmentioning
confidence: 99%
“…En España, la mejora genómica todavía no ha sido completamente implementada en el ganado ovino de leche, aunque hay razas que ya la tienen en marcha. Jurado (2017) expuso y habló sobre la situación y problemas principales de la implementación de la selección genómica en el ganado ovino de leche en España. Jurado refirió a que se habían realizado varios estudios preliminares de selección genómica en los candidatos a futuros sementales.…”
Section: El Sector Del Ganado Ovino De Leche En Españaunclassified
See 3 more Smart Citations